Analysis of Solar Powered Charging Station with Offgrid System for Two-Wheeled Electric Vehicle Needs at Telkom University Surabaya - Rifki Dwi Putranto; Hafidz, Isa; Faricha, Anifatul (Universitas Pahlawan Tuanku Tambusai, 2025)
This study focuses on the analysis of the needs and determination of the capacity of the solar power plant (PLTS) components used as an energy source at a public electric vehicle charging station (SPKLU) or often called a charging station to charge electric motorbike batteries at Telkom University Surabaya. Calculations are carried out to obtain: the area of ​​the solar module, the power required, the number of solar modules, the MPPT capacity, the backup battery, and the duration of charging the electric vehicle. The research method used is a research method with an approach calculation by comparing several similar references related to planning in building a PLTS with an offgrid system. The battery data collection method is carried out by observation, literature study and collection of weather condition data through the East Java BMKG. The results of the study show that with a solar intensity of Gav 4.32 kWh / m2 / day, a module array area of ​​5,268.3 m2 is required. With a sunlight intensity of 1000 W / m2, the power generated by the area is 1,053 Wp. The solar panel specifications use 375 WP, with a total of 3 panels arranged in series. The system can produce 1,122.98 Wp of power. The SCC produces 15.59 A. The charging time required is 7 hours and 30 minutes. Keyword: Battery, Charging Station, Electric Vehicle, PLTS